Birth weight and quality of life in midlife: a 50-year follow-up study of 2079 individuals in Denmark - Hegelund, Emilie Rune; Wimmelmann, Cathrine Lawaetz; Strizzi, Jenna Marie; Folker, Anna Paldam; Mortensen, Erik Lykke; Flensborg-Madsen, Trine (Quality of life research, 2020)
Purpose Low birth weight has been associated with a higher risk of reduced quality of life (QoL) in children, adolescents, and young adults, but the influence seems to diminish over time. However, previous studies have mainly focused on health-related QoL and compared individuals with low birth weight with individuals without low birth weight. The purpose of the present cohort study was to investigate the influence of the entire range of birth weights on three distinct measures of QoL in midlife. Methods The study population consisted of all live-born singletons from the Copenhagen Perinatal Cohort (CPC, 1959–1961) who participated in a 50-year follow-up examination in 2009–2011 ( N = 2079). Birth weight was measured by three pediatricians at birth. QoL was measured at the follow-up by the participants’ scores on three QoL self-report measures: The Satisfaction With Life Scale, the Vitality Scale of the Medical Outcomes Study 36-Item Short-Form Health Survey, and a single-item QoL measure based on the question: “How is your quality of life at the moment?”. General linear regression and binary logistic regression were used to estimate the association between birth weight and QoL in midlife. Results Small, curvilinear associations of birth weight with life satisfaction, vitality, and the single-item QoL measure were found, suggesting that both low and high birth weights increase the risk of low satisfaction with life, low vitality and low QoL. Conclusion The study findings suggest that low and high-range birth weight exert a lasting influence on distinct, but complementary aspects of QoL in midlife.